2007
DOI: 10.2353/ajpath.2007.061213
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Body Giant Cell Formation Is Preceded by Lamellipodia Formation and Can Be Attenuated by Inhibition of Rac1 Activation

Abstract: Macrophages that are recruited to the site of implanted biomaterials undergo fusion to form surfacedamaging foreign body giant cells. Exposure of peripheral blood monocytes to interleukin-4 can recapitulate the fusion process in vitro. In this study, we used interleukin-4 to induce multinucleation of murine bone marrow-derived macrophages and observed changes in cell shape, including elongation and lamellipodia formation, before fusion. Because cytoskeletal rearrangements are regulated by small GTPases, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 88 publications
(112 citation statements)
references
References 34 publications
7
105
0
Order By: Relevance
“…We observed that bone marrow-derived macrophages (BMDMs) stimulated in culture with cytokines to induce M1 or M2 polarization displayed markedly different cell morphologies, as has also been reported by other groups (15,16). Addition of LPS and IFN-γ, which stimulate M1 polarization, caused cells to flatten into a round, pancake-like shape within 24 h of stimulation.…”
Section: Macrophage Polarization State Is Associated With Changes In supporting
confidence: 78%
“…We observed that bone marrow-derived macrophages (BMDMs) stimulated in culture with cytokines to induce M1 or M2 polarization displayed markedly different cell morphologies, as has also been reported by other groups (15,16). Addition of LPS and IFN-γ, which stimulate M1 polarization, caused cells to flatten into a round, pancake-like shape within 24 h of stimulation.…”
Section: Macrophage Polarization State Is Associated With Changes In supporting
confidence: 78%
“…In contrast to ThioMΦ, BMM were stimulated with IL-4 and GM-CSF to induce macrophage fusion (Jay et al, 2007). We found that fusion was severely impaired in macrophages from CD36-KO mice compared with the wild-type control ( Fig.…”
Section: Macrophage Fusion Is Impaired In Cd36-ko Macrophagesmentioning
confidence: 79%
“…8 Moreover, MCP-1-null macrophages were deficient in IL-4 -induced activation of Rac1, and inhibition of Rac1 with the low-molecular-weight inhibitor NSC23766 attenuated FBGC formation in vitro and in vivo. In addition, in a separate study, lack of MMP-9 induction by MCP-1-null macrophages was observed under fusogenic conditions.…”
Section: Inhibition Of Rac-1 Leads To Reduction In Mmp-9 Expressionmentioning
confidence: 99%
“…8,12 Expanded cells (0.5 ϫ 10 6 per well) were plated on a 24-well non-tissue culture treated polystyrene plate (BD Biosciences, Franklin Lakes, NJ) in media containing 10 ng/mL rm GM-CSF and 10 ng/mL rm IL-4. To examine the role of TNF-␣ in fusion, in separate experiments, cells were incubated with increasing dosages (5, 10, or 50 ng/mL) of rm TNF-␣.…”
Section: In Vitro Fusion Assaymentioning
confidence: 99%
See 1 more Smart Citation